Trend Analysis of Research Articles Published in the Korean Journal of Women Health Nursing from 2013 to 2017 - Young Jin Lee; Seo Yun Kim; Saem Yi Kang; Yoo Jeong Kang; Lan Jin; Hee Yoen Jung; Hae Won Kim (Korean Society of Women Health Nursing, 2018)
PURPOSE: To analyze articles published in the Korean Journal of Women Health Nursing from 2013 to 2017 to determine the latest research trends and understand how 2013 Korea Women's Health Statistics were reflected in journal articles. METHODS: A total of 130 studies were analyzed. Research design, types of research, research framework, research subjects, characteristics of quantitative research, characteristics of qualitative research, and keywords were analyzed using a structured analysis format. RESULTS: Quantitative and qualitative research accounted for 83.8% and 13% of these 130 studies analyzed, respectively. Non-experimental and experimental research accounted for 70.7% and 13.1% of these studies, respectively. The most frequent study subjects were childbearing women (62.8%), including college students, mothers, and adults. A total of 69.1% of non-experimental research and 88.2% of experimental research used convenience sampling. Questionnaires were most frequently used for data collection. The most frequent keyword domain involved health-related concepts (41%) among nine domains and the most frequently used keyword was "women." CONCLUSION: This study suggest that further experimental research should be conducted in the future. Also, adolescent and the elderly women should be focused on as subjects in future studies based on results of 2013 Korean Women's Health Statistics.